CONTENTS OF CORRECTIVE PEDAGOGICAL WORK IN THE EDUCATION OF CHILDREN WITH SPECIAL EDUCATION NEEDS - Laylo Nurmukhamedova (The Bioscan, 2024)
Today, due to the great importance of the school period in ensuring that people with mental development problems actively participate in various social, economic and cultural relations of the society, have a happy marriage, and adapt to various life situations effectively, the reform of special education is the issue. special pedagogy and the public education system are considered urgent tasks.